Hubungan Antara Prilaku Merokok Dengan Kejadian Hipertensi - Rosadi, Erik; Putri, Anggy Utama (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Hypertension is a silent killer where the symptoms can vary for each individual and are almost the same as the symptoms of other diseases, hypertension is a condition without symptoms, where abnormally high pressure in the arteries causes an increased risk of stroke, aneurysm, heart failure, heart attack, Smoking habits are one of the factors causing hypertension. Nicotine content can increase heart rate and blood pressure. The aim of the research was to determine the relationship between smoking behavior and the incidence of hypertension, Kertapati sub-district, Palembang city. The research method uses a research design, namely a cross sectional study. The sample in this study was 88 respondents with a purposive sampling technique. The results obtained based on the chi-square test obtained a p-value = 0.001 0.05. So it can be concluded that there is a significant relationship between smoking behavior and the incidence of hypertension in Karya Jaya sub-district.